Study on thermal decomposition and characterization of palm oil waste and forestry residues - Siti Nor Fadhilah, Yasim (2015)
Currently, researchers try to find another alternative energy sources to reduce dependence on fossil fuels, and also to fill the gap left through depletion of oil, gas and coal after 2088 and onwards. Malaysia is a second largest palm oil producer with total of 5.33 million hectares palm oil plantation. Production of palm oil in year 2013 increases to 19.22 million tonne from 18.79 million tonne in year 2012. Meanwhile in year 2014, production predicted is more than 19.55 million tonne. From the increasing of palm oil production, it shows that production of palm oil waste (biomass) also increases. Due to the huge amount of biomass generated yearly, Malaysia has a potential to utilize the biomass efficiently and effectively as an alternative energy source to replace fossil fuels. However, biomass has several problems such as high moisture content, low calorific value, and low density as compared to fossil fuels, therefore pretreatment of biomass is required. In this study, torrefaction was used as a pretreatment method for biomass. Torrefaction is strongly depended on the thermal decomposition behavior and composition of lignocellulosic constituents, and thermal decomposition profile was studied by using thermogravimetric analyzer (TGA). In this study, all the material were dried at 105 ºC with moisture content left is less than 10%. After that, decomposition profile/region was monitored by using TGA Q500 with different heating rate which is 10 ºC/min and 20 ºC/min, initial temperature set at 30 ºC and final temperature at 600 ºC. Flow rate of nitrogen gas at 100 ml/min was used. In this work, four samples were used, which are empty fruit bunch (EFB), palm kernel shell (PKS), mersawa and durian. Decomposition region of biomass start with hemicellulose, followed by cellulose and then lignin being last to decompose. From TGA graph, below 100 ºC, biomass loss their weight 5 – 10% due to water evaporation. From 100 – 500 ºC, the weight loss about 70 – 80% was due to high volatile matter. Then, temperature above 600 ºC weight loss found to be 10 – 20%. Study also revealed that the rate of decomposition EFB is faster than PKS due to high content of hemicellulose. Mass composition of lignocellulosic in biomass affects the rate of decomposition because the hemicelluose can enhance the decomposition rate and the lignin can reduce the decomposition rate of biomass. This TGA analysis is useful to design the torrefaction (mild pyrolysis), pyrolysis and gasification unit according to biomass thermal stability. In order to differentiate, investigate, or comparing decomposition characteristic between biomass, more biomass sample can be tested (other type of biomass) to see the trend of torrefaction process.